Hybrid event beds in the proximal to distal extensive lobe domain of the coarse-grained and sand-rich Bordighera turbidite system (NW Italy). (September 2017) - Mueller, Pierre; Patacci, Marco; Di Giulio, Andrea
Abstract: The Upper Cretaceous Bordighera Sandstone of NW Italy is a coarse-grained, sand-rich elongated turbidite system (ca. 15 × 45 km in outcrop) up to 250 m thick, interpreted to have been deposited in a trench setting. The siliciclastic succession interfingers with muddy calcareous turbidites, which become more abundant toward the lateral and distal domains. Bed type associations allow the distinction of a proximal channelized domain which transitions to a more distal lobe domain, characterized by abundant mudclast-rich sandstones and by bipartite and tripartite beds with a mud-rich middle or upper division (hybrid event beds). The transition between the proximal and distal domains occurs over a relatively limited spatial extent (ca. 5 km). The presence of lenticular bed-sets made up of coarse grained and mud-poor sandstones throughout the distal domain suggests that distributary channels were present, indicating sediment bypass further down-dip toward the most distal and not preserved parts of the system. Hybrid event beds - commonly associated with distal and marginal fan environments such as fan fringes - are present throughout the lobe domain and extend for up to ca. 30 km in down-dip distance. They are more abundant in the proximal and axial depositional lobe domain and their appearance occurs within a short basin-ward distance from the inferred channel-lobe transition zone. Flow expansion at the termination of the channelized domain and the enhanced availability of cohesive substrate due to the presence of intra-basinal muddy calcareous beds are interpreted as the key controls on the widespread occurrence of mudclast-rich and argillaceous sandstone beds. The abrupt appearance and the persistent occurrence of such beds across an extensive domain have implications for characterizing bed-scale (sub-seismic) heterogeneity of deep-water clastic hydrocarbon reservoirs. Graphical abstract: Highlights: Multi-scale approach illustrating facies heterogeneity due to hybrid event bed emergence. Sand-rich turbidite system's characteristics rapidly shift within a short down-dip distance. Facies heterogeneity occurs at the bed-scale (i.e. sub-seismic scale). Idealized down-current and along-current stacking pattern trends for sand-rich HEB-prone turbidite systems are proposed.